FORMULATION OF VIRGIN COCONUT OIL (VCO) AND ALOE VERA (ALOE VERA l.) AS A POMADE - M Maryan Fitra; H Harunsyah; S Salmyah (Jurnal Sains dan Teknologi Reaksi, 2026)
Developments in the cosmetics industry, particularly in hair care products, have driven the creation of innovative, natural-based formulations that are safe and environmentally friendly. One of the most popular products is pomade, especially among men. However, many pomades available on the market still contain synthetic ingredients that can cause long-term side effects. This study aims to formulate pomade using natural active ingredients, namely virgin coconut oil (VCO) and aloe vera (Aloe vera L.), and to evaluate the effect of varying the volume of these two ingredients on the physical characteristics and total antioxidant content of the product. VCO was used in volume variations of 0; 5; 10; 15; and 20 ml, while aloe vera was used in variations of 0; 2.5; 5; 7.5; and 10 ml. The parameters tested included pH, melting point, ash content, homogeneity, organoleptic properties, and total antioxidants using the DPPH method. The results showed that the addition of VCO and aloe vera affected the physical properties and antioxidant content of the pomade. The best formula was obtained from a combination of 15 ml of VCO and 10 ml of aloe vera, with a pH of 6.5; melting point of 43°C; ash content of 0.08%; and the highest antioxidant content of 1.5350 mg of vitamin C equivalent per gram. Most samples were homogeneous and organoleptically acceptable, except at the highest concentration, which showed heterogeneity. The combination of VCO and aloe vera proved effective in producing a stable pomade. Keywords: Aloe vera, Antioxidant, Natural cosmetics, Pomade, Virgin coconut oil